2016
DOI: 10.1002/prca.201600039
|View full text |Cite
|
Sign up to set email alerts
|

Purine biosynthesis is the bottleneck in trimethoprim‐treated Bacillus subtilis

Abstract: The frequently prescribed antibiotic trimethoprim causes purine depletion in B. subtilis, which can be complemented by supplementing purines to the medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…To identify commonalities of the physiological impact of allicin to that of other antibacterial agents, we compared the proteomic response to allicin to a response library containing 44 proteomic responses of B. subtilis to known antimicrobial agents . Regarding the number of induced proteins, with 56 marker proteins, allicin evoked the most complex response in B. subtilis among the tested compounds.…”
Section: Resultsmentioning
confidence: 99%
“…To identify commonalities of the physiological impact of allicin to that of other antibacterial agents, we compared the proteomic response to allicin to a response library containing 44 proteomic responses of B. subtilis to known antimicrobial agents . Regarding the number of induced proteins, with 56 marker proteins, allicin evoked the most complex response in B. subtilis among the tested compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of THF biosynthesis leads to cell death as a result of purine auxotrophy and consequent thymine deficiency (“thymineless death”) (24). In B. subtilis , purine biosynthesis is the primary bottleneck caused by 10f-THF depletion after treatment with antifolates, such as trimethoprim (TMP) (25). 10f-THF is used as a formyl group donor at two steps in purine biosynthesis (Fig 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Even in the presence of CAA, all colonies were small, and only about 20% of those growing on trimethoprim (6 g/ml) carried a stable thyB insertion. Work in E. coli as well as in B. subtilis has shown that disruption of the folate pathway can lead to depletion of key amino acids as well as of purines and pyrimidines (33,34). Trimethoprim-mediated inactivation of dihydrofolic acid reductase (DHFR) would deplete intracellular levels of tetrahydrofolic acid (THF), methylenetetrahydrofolic acid (MTHF), and dihydrofolate (DHF).…”
Section: Resultsmentioning
confidence: 99%